Neuroimmune dynamics and brain aging: mechanisms and consequences - Müller, Ludmila; Di Benedetto, Svetlana; Müller, Viktor (Frontiers in Aging Neuroscience, 2025)
Brain aging is accompanied by profound changes in neuroimmune interactions that shape the balance between resilience and vulnerability. Under healthy conditions, glial cells, neurons, vascular elements, and peripheral immune inputs cooperate to sustain homeostasis. With advancing age, however, immune remodeling and systemic inflammaging drive shifts in microglial surveillance, astrocytic reactivity, and neuronal susceptibility, creating conditions that compromise synaptic function and cognitive performance. These processes unfold along a continuum, from subtle impairments in normal aging to maladaptive dynamics that accelerate neurodegenerative disease. Sex differences, epigenetic regulation, and systemic influences—including the gut microbiome, metabolic state, and lifestyle factors—further modulate these trajectories. Here, we synthesize current knowledge on the cellular, systemic, and molecular mechanisms that govern neuroimmune aging, emphasizing how their dysregulation contributes to cognitive decline and disease vulnerability. We also highlight emerging conceptual frameworks, such as multilayer network modeling and resilience biomarkers, that provide a foundation for integrative approaches to brain aging. Understanding these interconnected systems underscores the necessity of viewing brain aging not solely through a CNS-centric lens, but as a networked process influenced by distal organs, circulating immune cells, microbial communities, and lifestyle factors—setting the stage for integrative models of neuroimmune dynamics in aging. Clarifying how these dynamic interactions unfold and what their consequences are is essential for developing strategies to preserve cognitive health and mitigate the burden of neurodegeneration in an aging society.